The Use of Hungarian and Serbian in the City of Szabadka/Subotica : An Empirical Study - Siarl Ferdinand; Flora Komlosi (Hungarian Cultural Studies, 2017)
In this study Ferdinand and Komlosi analyze the use of Hungarian and Serbian in the city of Szabadka/Subotica, which is located in the Serbian region of Northern Vajdaság/Vojvodina. A mostly Hungarian speaking city for centuries, Szabadka/Subotica suffered the strong pro-Serbian language policy implemented by the Yugoslavian government from the end of the First World War until the dismantlement of Yugoslavia in the 1990s, which gave Hungarian and other local minority languages a second chance to survive. Nowadays, Szabadka/Subotica is home to two main language groups, southern Slavic languages such a Serbian and Croatian (over sixty per cent) and Hungarian (thirty three per cent). Although Ferdinand and Komlosi employed official figures from the Serbian censuses to determine the size of each group, the situation of each language was mapped through empirical observation of language use in informal conversations, in official signage, and in permanent as well as temporary commercial signage. The results show that the role of Serbian (mostly written in Latin script) is dominant in almost all spheres of public life and as a lingua franca among various groups. Nevertheless, Hungarian maintains a strong presence in the city, especially in the center and in its northwestern districts. In this paper, Ferdinand and Komlosi aim to contribute to a better general understanding of group dynamics in bilingual settings and, specifically, to provide a clearer view of the language situation in one of the Hungarian-speaking regions lost by the historic Kingdom of Hungary after World War I.